Knowledge, attitude, and practice of white coat use among medical students during clinical practice (LAUNDERKAP): A cross-sectional study - Chan, Chee K.; Lam, Thian Y.; Langkeas, Mohanavel; Jeffrie, A. Ghani; Afieq, S.K. Anuar; Lee, Choon J.; Loo, Qing Y.; Heng, Wei Y.; Lai, Pauline S.M. *; Koh, Kwee C.; Loh, Huai H.; Najma, Kori; et al. (Elsevier, 2024)
Background Recent studies found white coats to be reservoirs for bacteria and medical students did not conform to proper hygiene measures when using these white coats. We investigated the knowledge, attitude, and practice (KAP) of medical students toward white coat use in clinical settings (LAUNDERKAP).